2016
DOI: 10.1200/jco.2015.62.6630
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of the Combination of Recurrence Score and Quantitative Estrogen Receptor Expression (ESR1) on Predicting Late Distant Recurrence Risk in Estrogen Receptor–Positive Breast Cancer After 5 Years of Tamoxifen: Results From NRG Oncology/National Surgical Adjuvant Breast and Bowel Project B-28 and B-14

Abstract: Purpose We determined the utility of the 21-Gene Recurrence Score (RS) in predicting late (> 5 years) distant recurrence (LDR) in stage I and II breast cancer within high and low-ESR1–expressing groups. Patients and Methods RS was assessed in chemotherapy/tamoxifen-treated, estrogen receptor (ER) –positive, node-positive National Surgical Adjuvant Breast and Bowel Project B-28 patients and tamoxifen-treated, ER-positive, node-negative B-14 patients. The association of the RS with risk of distant recurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 32 publications
0
67
0
2
Order By: Relevance
“…The 21-gene recurrence score (RS) assay (Genomic Health) is calculated on the basis of the RNA expression levels of 21 genes and has been validated in T1-2 N1 breast cancer to be prognostic of LRR, disease-free survival, and overall survival (OS; refs. [6][7][8][9][10]. Other gene profiling assays have demonstrated similar correlations (11)(12)(13).…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…The 21-gene recurrence score (RS) assay (Genomic Health) is calculated on the basis of the RNA expression levels of 21 genes and has been validated in T1-2 N1 breast cancer to be prognostic of LRR, disease-free survival, and overall survival (OS; refs. [6][7][8][9][10]. Other gene profiling assays have demonstrated similar correlations (11)(12)(13).…”
Section: Introductionmentioning
confidence: 72%
“…The 21-gene RS assay has been validated as an independent prognosticator of LRR, distant recurrence, and OS in women with node-positive ER-positive breast cancer (6)(7)(8)(9)(10). Furthermore, RS has been shown to predict benefit to adjuvant systemic chemotherapy for women with node-negative cancer, and is endorsed by the ASCO 2016 Focused Guideline Update to be used in decision making regarding systemic treatment (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results strongly suggest that the Oncotype RS is not a solid candidate for the prediction of late distant recurrence in women with ER-positive disease. However, more recently, the Oncotype RS was evaluated in patients from the NSABP B-28 and B-14 trials for the prediction of late distant recurrence within low and high ESR1 levels [16]. The study found that Oncotype RS is strongly prognostic for late distant recurrence in women with a high ESR1 level (cut-off 9.1) and that extended tamoxifen therapy is warranted in those with high expression of ESR1 and intermediate/high risk patients.…”
Section: Biomarker Assaysmentioning
confidence: 89%
“…In an analysis of 665 ER + node-negative patients in the TransATAC study, Oncotype DX ® was not found to have any significant effect on the prediction of late metastases more than 5 years after successful surgery [13]. By contrast, a prognostic influence of Oncotype DX ® on late distant metastases was demonstrated, depending on the gene expression of the estrogen receptor (ESR1) [14].…”
Section: Mammatyper ®mentioning
confidence: 99%